The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/jcm.01821-18
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum and Bronchoalveolar Lavage Fluid Galactomannan in Diagnosis of Chronic Pulmonary Aspergillosis

Abstract: The value of serum and bronchoalveolar lavage fluid galactomannan (BALF-GM) in diagnosing chronic pulmonary aspergillosis (CPA) remains unclear. Here, we study the diagnostic efficacy of GM in the diagnosis of CPA. We included consecutive treatment-naive subjects with CPA. For calculating the specificity of serum GM, we enrolled diseased controls (minimally symptomatic subjects previously treated for pulmonary tuberculosis, not meeting the criteria for CPA). To calculate the specificity of BALF-GM, subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 22 publications
(38 reference statements)
1
50
0
Order By: Relevance
“…In the current study, BALF‐GM performed better than serum GM, like in subjects with CPA . The best diagnostic performance of BALF‐GM was at a cut‐off ODI value of 2.5.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…In the current study, BALF‐GM performed better than serum GM, like in subjects with CPA . The best diagnostic performance of BALF‐GM was at a cut‐off ODI value of 2.5.…”
Section: Discussionmentioning
confidence: 43%
“…6,[9][10][11][22][23][24][25] In a previous study, we have shown that serum and BALF-GM at a cut-off value of 0.55 and 1.4, respectively, provided the best sensitivity and specificity in diagnosing CPA. 6 The values of serum and BALF-GM for diagnosing SA were also different in this study, as CPA is minimally invasive compared to acute or subacute invasive pulmonary aspergillosis. 6 One retrospective study has evaluated the utility of serum and BALF-GM in diagnosing SA.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations